Rational selection of bioactive principles for wound healing applications: Growth factors and antioxidants - Viaña Mendieta, Pamela (2022)
Wound healing is a complex process of communication between growth factors, reactive species of oxygen, cells, signalling pathways, and cytokines in the extracellular matrix, in which growth factors are the key regulators. In humans, the main regulators of the cellular responses in wound healing are five growth factors, namely EGF, bFGF, VEGF, and TGF-β1. On the other hand, antioxidants such as astaxanthin, beta-carotene, epigallocatechin gallate, delphinidin, and curcumin have been demonstrated to stimulate cell proliferation, migration and angiogenesis, and control inflammation, to suggest a practical approach to design new strategies to treat non-healing cutaneous conditions. Based on the individual effects of growth factors and antioxidants, it may be envisioned that the use of both types of bioactives in wound healing formulations may have an additive or synergistic effect on the healing potential. This review addresses the effect of growth factors and antioxidants on wound healing-related processes. Furthermore, a prospective on their potential additive or synergistic effect on wound healing formulations, based on their individual effects, is presented. This may serve as a guide for the development of a new generation of wound healing formulations.